Structural shocks and the comovements between output and interest rates - Elmar Mertens (Swiss National Bank, Study Center Gerzensee, 2005)
Stylized facts on U.S. output and interest rates have so far proved hard to match with simple DSGE models. I estimate covariances between output, nominal and real interest rate conditional on structural shocks, since such evidence has largely been lacking in previous discussions of the output-interest rate puzzle. Conditional on shocks to technology and monetary policy, the results square with simple models. Moreover, permanent inflation shocks accounted for the counter-cyclical and inversely leading behavior of the real rate during the Great Inflation (1959-1979). Over the Great Moderation (1982-2006), technology shocks were more dominant and the real rate has been pro-cyclical.
Keywords: 330; Interest Rates; Business Cycles; Bandpass Filter; Structural VAR; News Shocks